Analysis of the developmental role of taxes in national income in Iraq for the period (2010-2023) (Czech Journal of Multidisciplinary Innovations, 2025)
Taxes are not merely a financial instrument or a sum forcibly deducted from individuals. Rather, taxes are an important financial channel through which public finance makers monitor all economic events and seek to finance sustainable economic development paths and plans. The research aims to monitor the developmental role of taxes in stimulating national income and, consequently, improving economic indicators in general. The research assumes that the effective role of taxes enables them to achieve this developmental role in stimulating national income in the Iraqi economy and financing sustainable development projects. Specific indicators were adopted for the research variables to validate the hypothesis, and a quantitative approach was used to reinforce these results. The research concluded that the Iraqi economy is losing the developmental role of taxes in generating a stable national income capable of improving opportunities for sustainable development. It recommended adopting a technological approach to revitalizing the role of taxes to eliminate widespread red tape and bureaucracy, thus serving as a path toward achieving the desired goal.